The efficacy of vitamin C infusion in reducing post intubation sore throat - Jarahzadeh, Mohammad Hossein; Mousavi bioki, Mohammad Hossein; Abbasi, Hamidreza; Jafari, Mohammad Ali (Medicinski časopis, 2020)
Background Vitamin C may be a beneficial adjunct for decreasing of score throat following tracheal intubation. Therefore, the aim of this study was to evaluate the effect of vitamin C infusion onpost intubationsore throat reduction. Materials and Methods This double-blind randomized study was conducted on 70 patients undergoing elective laparoscopic surgery in ShahidSadoughi Hospital. Patients were allocated into two groups (case and control). All patients received 2 mg midazolam and 100 microgram fentanyl citrate premedication. Thirty min after induction of anesthesia,5 mg morphine was given to all patients. In the next step, case group received vitamin C (2 g) mixed with normal saline for a total injection volume of 500 mL during 30 min and those in control group received normal saline without vitamin C. Results In current study, no remarkable difference was observed between case and control groups, considering age, sex and BMI (p>0.05). Significant difference was observed between case and control groups in terms of postoperative sore throat at  specified time including 1, 6 and 24 hours .Asignificant difference was seen between case and control groups with respect to postoperative score pain at specified time (p0.05). Conclusion According to results of this study, the use of vitamin C reduced the incidence of sore throat and score pain in patients undergoing laparoscopic surgery.It seems that vitamin C can decrease morphine indicated for postoperative pain.